SUBSTANTIATION OF RULES FOR SETTING OF RETAINING PROTECTIVE BUILDINGS AGAINST LANDSLIDE ON HIGHWAYS IN MOUNTAINOUS AREAS - Тymchenko, О.; Тимченко, О. Н. (Харьковский национальный автомобильно-дорожный университет, 2016)
The grounding of choice of necessary construction of retaining protective buildings and their location on landslide areas is carried out. It has been noted that the efficiency of protective measures is provided on condition of landslide process development studying, the geological structure of the sliding dangerous territory, the form and conditions of the glide surface and studying of the water-bearing horizons.
ОБОСНОВАННЫЕ ПРИНЦИПЫ НАЗНАЧЕНИЯ УДЕРЖИВАЮЩИХ ПРОТИВООПОЛЗНЕВЫХ СООРУЖЕНИЙ НА АВТОМОБИЛЬНЫХ ДОРОГАХ В ГОРНОЙ МЕСТНОСТИ
ОБҐРУНТОВАНІ ПРИНЦИПИ ПРИЗНАЧЕННЯ ЗАТРИМУЮЧИХ ПРОТИЗСУВНИХ СПОРУД НА АВТОМОБІЛЬНИХ ДОРОГАХ У ГІРСЬКІЙ МІСЦЕВОСТІ
Keywords: retaining building against landslide; landslide and sliding dangerous territory; choice of protective building; удерживающее противооползневое сооружение; оползневая и оползнеопасная территория; выбор защитного сооружения; затримуюча протизсувна споруда; зсувна та зсувонебезпечна територія; вибір захисної споруди; 625.72